Left-sided approach of AV junction ablation for drug refractory atrial fibrillation (Faculty of Medicine Universitas Indonesia, 2006)
AV junction ablation has been proven effective to treat symptomatic atrial fibrillation refractory to antiarrhythmias or fail of pulmonary vein isolation. However, about 15% of conventional right-sided approach AV junction ablation failed to produce complete heart block. This study aimed to characterize His bundle potential at ablation site during conventional or left-sided approach of AV junction ablation. Twenty symptomatic AF patient (age of 60.5 ± 9.28 and 11 are females) underwent conventional AV junction ablation. If 10 applications of radiofrequency energy are failed, then the ablation was performed by left-sided approach. Seventeen patients are successfully ablated by conventional approach. In 3 patients, conventional was failed but successfully ablated by left-sided approach. The His bundle amplitude at ablation site was significantly larger in left-sided than correspondence right-sided (16.0 ± 4.99 mm vs. 6.9 ± 4.02 mm respectively, p = 0.001, 95% CI -14.0 to -4.3). ROC analysis of His bundle potential amplitude recorded from right-sided revealed that cut off point of > 4.87 mm given the sensitivity of 81.3% and specificity of 53.8% for successful right-sided approach of AV junction ablation. In case of failed conventional approach, the left-sided approach is effective for AV junction ablation. An early switch to the left-sided approach may avoid multiple RF applications in patients with a low amplitude His-bundle potential (< 4.87 mm). (Med J Indones 2006; 15:109-14)